The Imago Dei and Philosophical Anthropology - Mouw, Richard J. (Christian scholar's review, 2012)
Theologians have long explored the meaning of the biblical notion of the imago dei for our understanding of the complexities of human personhood. In recent years the focus has often been on the “functional-relational,” as opposed to an “ontological,” account of the imago. Richard J. Mouw reflects here on the ways in which these biblical-theological explorations can cast light on the issues traditionally discussed by philosophers in the questions they raise about what, if anything, comprises the uniqueness of the human person.